Faktor-Faktor Yang Mempengaruhi Indeks Harga Saham Gabungan - Augustpaosa Nariman, Hendang Tanusdjaja, (Jurnal Ekonomi, 2019)
The growth of the stock market in Indonesia from the Composite Stock Price Index (CSPI) showed quite fantastic in the last ten years after experiencing a downturn in the 2008 global financial crisis. The stock investment in the capital market is not the only type of financial investment, there is another type, namely Indonesia Bank Certificate (SBI) and money market measured by exchange rates. This study aims to find out how the SBI interest rate, exchange rate, money supply (M2) and inflation affect the JCI in the 2011-2015 periods. By using SPSS V20, it was found that in the period of SBI interest rate, exchange rate, money supply (M2) and inflation rate had no effect on the CSPI. This is due to the level of return on the capital market is greater than the SBI interest rate and exchange rate difference, while the number of transactions on the Indonesia Stock Exchange is still dominated by foreign investors, M2 does not affect the CSPI, and they are generally traders rather than investors, thus the inflation rate affects the company's growth was slightly ignored.